Plays of sanaa shalan style and content an analytical study on her selected works - Abbas P.M (Department of Arabic, University of Calicut, 2025)
This study examines the development of Arabic theatre, with particularreference to the influence of Brechtian epic theatre, focusing on the works of Jordanianplaywright Sanaa Shalan. It traces the evolution of drama from classical Greek originsto Brecht’s revolutionary techniques, such as the alienation effect, episodic structure,and audience engagement, which shift focus from emotional immersion to criticalthinking.The study is organized into six chapters. First Chapter explores the origin anddevelopment of theatre and drama, and its role in Arabic literature. Second Chapterfocuses on Arabic drama in Jordan, its evolution, and key figures. Third Chapterstudies Sanaa Shalan, her life, literary achievements, and plays. Fourth Chapteranalyses the stylistic features of her works, particularly Brechtian techniques and self-reflective dramaturgy. Fifth Chapter examines thematic aspects, including socialissues, and Palestinian identity. Sixth Chapter presents critical analyses of selectedplays, including (Selfie Mae Albahr and Muhakamat Al Ism X).In conclusion, this study affirms that Sanaa Shalan’s plays address women’soppression, refugee crises, identity loss, social injustice, and the Palestinian struggle,while employing Brechtian strategies to engage audiences intellectually and ethically.The study concludes that her works significantly enrich modern Arabic theatre byadapting epic theatre techniques to Arab and Palestinian contexts.
Keywords: Sanaa Shalan; Arabic theatre; Brechtian epic theatre; Alienation effect; Jordanian drama; Women’s issues